INVESTIGATION OF THE COMBUSTION CHARACTERISTICS OF RIGID POLYURETHANE FOAM WITH ADDED NATURAL FILLER POWDER - J. Mohammed, Ahmed; K. Ibrahim , Ibrahim (Antis-Publisher, 2025)
Objective: This study aims to investigate the combustion characteristics of rigid polyurethane foam (RPUF) composites with the addition of natural filler powder, specifically perlite stone powder, to evaluate its effect on fire resistance. Method: RPUF composites were prepared with varying weight percentages of perlite stone powder (0%, 5%, 10%, 15%, 25%, and 35% w/w) with particle sizes ≤ 125 μm. Combustion performance was assessed by measuring the average burning time (ATB) and the percentage of time burning under controlled conditions. Results: The results revealed that the average burning time significantly decreased as the perlite filler content increased. While the composite without filler (0%) exhibited the highest ATB, a notable reduction in combustion duration was observed with increasing filler content, reaching approximately 20 seconds at 35% perlite. This indicates an inverse relationship between filler content and combustion duration, suggesting improved fire resistance with higher filler concentrations. Novelty: This study provides new insights into the fire-retardant potential of natural fillers like perlite stone powder in RPUF composites, highlighting their effectiveness in enhancing thermal stability and reducing flammability, which has promising implications for safer material applications in construction and insulation industries.